A novel HIV treatment model using private practitioners in South Africa. Issue 2 (16th February 2012) - Innes, Craig; Hamilton, Robin; Hoffmann, Christopher J; Hippner, Piotr; Fielding, Katherine; Grant, Alison D; Churchyard, Gavin J; Charalambous, Salome
Abstract : Objectives: The extent of the HIV epidemic in South Africa may render the public sector capacity inadequate to manage all patients requiring antiretroviral treatment (ART). Private practitioners are an underutilised resource. Methods: The authors developed a model of care using 72 private practitioners in five provinces in urban and rural areas of South Africa with centralised clinical support, training, pharmacy control and data management. The authors describe the programme, its quality control measures and patient outcomes using a cohort analysis. Results: Between January 2005 and December 2008, 9102 individuals were started on ART, 62% female, median age 34 years, median viral load 50 655 copies/ml and median baseline CD4 count 123 cells/μl. Retention (alive and in care) after 12 months was 63% in the 2005 cohort (646 of 1026) and remained similar in the other calendar years, 58%, 68% and 64% in 2006, 2007 and 2008, respectively. After 36 months, retention was 50% and 41% for those enrolled in 2005 and 2006, respectively. The percentage virally suppressed remained similar at 6 months, 82% vs 84%, 84% and 85% from 2005, 2006, 2007 to 2008, respectively, p=0.66; but improved slightly at 12 months, 78% vs 83%, 83% and 84% from 2005 to 2008, p=0.05. At 36 months, it was 84% and 82% for the 2005 and 2006 cohorts, respectively. Conclusions: The results show that a well-managed private practitioner model can achieve comparable results to public services, although long-term retention needs further evaluation. This model of ART delivery can be used to expand access to ART in areas where the public sector is unable to meet the demand.